2022
DOI: 10.21037/atm-22-256
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation study based on NRS 2002, OPNI, and their combined use in patients with adverse drug reactions after chemotherapy: a cross-sectional study

Abstract: Background: It is important to assess the nutritional status of patients who have experienced adverse drug reactions (ADRs) after chemotherapy. We aimed to explore the nutritional status of patients who developed ADRs after chemotherapy, using the Nutritional Risk Screening 2002 (NRS 2002) tool, the Onodera Prognostic Nutrition Index (OPNI), and their combined application.Methods: NRS2002 screening and OPNI calculation for patients before chemotherapy. Patients with ADRs after chemotherapy were grouped accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…This downward trend in nutritional risk prevalence among OC women as chemotherapy progressed is noteworthy. Bian et al [ 21 ] reported a similar prevalence of nutritional risk (21.0%) before chemotherapy in cancer patients. The ascending trend observed in our study aligns with research by Gupta et al [ 12 ], who found that the malnutrition prevalence decreased from 53.1% at admission to 35.7% at 3 months in OC women following chemotherapy, indicating an improved nutritional status.…”
Section: Discussionmentioning
confidence: 92%
“…This downward trend in nutritional risk prevalence among OC women as chemotherapy progressed is noteworthy. Bian et al [ 21 ] reported a similar prevalence of nutritional risk (21.0%) before chemotherapy in cancer patients. The ascending trend observed in our study aligns with research by Gupta et al [ 12 ], who found that the malnutrition prevalence decreased from 53.1% at admission to 35.7% at 3 months in OC women following chemotherapy, indicating an improved nutritional status.…”
Section: Discussionmentioning
confidence: 92%